Del espacio público en Bogotá en el siglo xx: una mirada histórica desde las prácticas sociales - Cuervo Prados, Mónica (Folios, revista de la Facultad de Comunicaciones y Filología, 2010)
This article presents a theoretical and methodological view of some results and recommendations obtained in the research: The uses of public space in Bogota en the 20th. Century: a historical view form social practices, pedagogical implications for the city. It studies the city ́s social history, as well as its communicational strategies, ur-ban pedagogy and the importance of identity and social practices its citizens.